A STUDY ON IMPACT OF ONLINE SERVICES OF PUBLIC AND PRIVATE SECTOR BANKS ON CUSTOMER SATISFACTION IN BENGALURU CITY - Kumar N, Harish (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Online banking services has many advantages over other traditional banking delivery methods. Online banking services provides banks with an increased customer base, cost savings, mass customization, product innovations, improved marketing, and communication, the ability to develop non-core businesses, and the ability to offer services regardless of geography and time constraints. With the development of new technology, Online banking services is expected to become a major banking method for customers. Online banking services reduces costs by providing customers with another means of accessing their accounts without physically visiting a bank. The main purpose of this study is to analyze impact of Online services of public and private sector banks on customer satisfaction in Bengaluru City and to measure their impact on customers in terms of customer satisfaction. 100 respondents each banking sectors (Public and private sector) who are using online banking services are chosen as a sample study. Regression analysis was used to find out the influence of online services on customer satisfaction. The research revealed that, the unique contribution for the variables of online services provided by public sector banks such as online loan services, FASTAG – recharge services, SMS banking services, online bill payments services and deposit services in predicting overall customer satisfaction in public sector Banks. The unique contribution for the variables of online services provided by private sector banks such as online banking services, Bharat Bill Pay-UPI Services, mobile banking/app services, ATM services and debit and credit card services, FASTAG – recharge services, online bill payments services in predicting overall customer satisfaction in private sector banks.